2020
DOI: 10.1016/j.ijnss.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Professional nurses’ facilitation of self-care in intensive care units: A concept analysis

Abstract: Objective This article aims to provide an in-depth analysis of the concept of self-care and outline its defining attributes, antecedents, consequences and empirical referents. Methods The literature was searched electronically using databases such as CINAHL, Medline, Psych INFO, ERIC, ScienceDirect, Amed, EBSCO (Health Source: Nursing and Academic Edition), Sage, Ujoogle and Google Scholar. Articles from 2013 to 2020 were searched to target recent and up-to-date informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Therefore, they are prone to experience emotional and mental exhaustion and fatigue, which affects their ability to care for themselves. Mindful self-care practices prevent the onset of mental health symptoms, mitigate professional burnout, and improve productivity and resilience in nurses, thereby enabling them to provide safe and effective patient care (Chipu & Downing, 2020; Roux & Benita, 2020). Practicing self-care enables nurses to ameliorate the undesirable and damaging effects of working in stressful environments (Linton & Koonmen, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, they are prone to experience emotional and mental exhaustion and fatigue, which affects their ability to care for themselves. Mindful self-care practices prevent the onset of mental health symptoms, mitigate professional burnout, and improve productivity and resilience in nurses, thereby enabling them to provide safe and effective patient care (Chipu & Downing, 2020; Roux & Benita, 2020). Practicing self-care enables nurses to ameliorate the undesirable and damaging effects of working in stressful environments (Linton & Koonmen, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with previous studies. Chipu and Downing (2020) noted that nurses' self-care behaviors and practices are affected by their gender, age, clinical and professional experience, preference in activities, life choices, and educational levels. Hatch et al (2018) conducted a cohort survey of 402 nurses in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few explanations can be advanced. Research on self-care indicated that patients with high self-care abilities often had an increased self-esteem (Chipu & Downing, 2020). In Chinese traditional beliefs, taking breaks during daily activities can be seen as a reflection of low self-competence, especially by older people.…”
Section: Discussionmentioning
confidence: 99%
“…In the same breath, healthcare professionals, particularly professional nurses, have neglected the self-care concept; their focus is primarily on the nurse’s pledge of service, which states that patient care is their priority. 2 According to Younas, 1 nurses and nursing students tend to focus on their patients’ self-care and often pay little to no attention to their well-being. However, the best way to care for patients is to care for ourselves as healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%